STUDI PERBANDINGAN KOMPETENSI PRAKTIK KELISTRIKAN OTOMOTIF MAHASISWA LULUSAN SMA DAN SMK PADA PROGRAM STUDI PENDIDIKAN TEKNIK MESIN JPTK FKIP UNS - Saryatun, Saryatun (Jurnal Nosel, 2015)
The purpose of this research was to know there any differences of Mechanical Engineering JPTK FKIP UNS student competence between graduates from Senior High School and Vocational High School in Electrical Outomotive Practice. This study was quantitative research. The method used in this research was descriptive. Population in this study were all of student in Automotive Concentration Mechanical Engineering Education program year on 2011,there are 23. Samples were taken with a total sample technique. The technique of collecting data questionnaires. The validity of questionnaires research instruments was using the product moment correlation approach of pearson. The validity instrument test with a significance level of 5% in order to get the valve of r product moment of 0,444. Reliability test was using the Alpha formula. The technique of data analysis in this research is using descriptive analysis. Based on this research concluded: There are differences Mechanical Engineering JPTK FKIP UNS student competence between graduates from High School and Vocational High School in Electrical Outomotive Practice.Vocational High School graduate student competency better than High School. This consists with result of the measuring instrument indicator, while Vocational High School graduates at the high category with acquisition of a percentage of 50%, and High School 38.46%. Starter system indicator, Vocational High School graduates at the high category with acquisition of a percentage of 80%, while High School graduates in middle category percentage of 84.62%. Conventional ignition system indicator on vocational graduates are in high category while the acquisition of a percentage of 70%, but High School 53.84%. Engine analysis indicator, Vocational High School graduates at the high category while the acquisition of a percentage of 60%, but High School 46.15%.